Clinical features and outcome of 6 new patients carrying de novo KCNB1 gene mutations. (December 2017) - Marini, Carla; Romoli, Michele; Parrini, Elena; Costa, Cinzia; Mei, Davide; Mari, Francesco; Parmeggiani, Lucio; Procopio, Elena; Metitieri, Tiziana; Cellini, Elena; Virdò, Simona; De Vita, Dalila; et al.
Abstract : Objective: To describe electroclinical features and outcome of 6 patients harboring KCNB1 mutations. Methods: Clinical, EEG, neuropsychological, and brain MRI data analysis. Targeted next-generation sequencing of a 95 epilepsy gene panel. Results: The mean age at seizure onset was 11 months. The mean follow-up of 11.3 years documented that 4 patients following an infantile phase of frequent seizures became seizure free; the mean age at seizure offset was 4.25 years. Epilepsy phenotypes comprised West syndrome in 2 patients, infantile-onset unspecified generalized epilepsy, myoclonic and photosensitive eyelid myoclonia epilepsy resembling Jeavons syndrome, Lennox-Gastaut syndrome, and focal epilepsy with prolonged occipital or clonic seizures in each and every one. Five patients had developmental delay prior to seizure onset evolving into severe intellectual disability with absent speech and autistic traits in one and stereotypic hand movements with impulse control disorder in another. The patient with Jeavons syndrome evolved into moderate intellectual disability. Mutations were de novo, 4 missense and 2 nonsense, 5 were novel, and 1 resulted from somatic mosaicism. Conclusions: KCNB1 -related manifestations include a spectrum of infantile-onset generalized or focal seizures whose combination leads to early infantile epileptic encephalopathy including West, Lennox-Gastaut, and Jeavons syndromes. Long-term follow-up highlights that following a stormy phase, seizures subside or cease and treatment may be eased or withdrawn. Cognitive and motor functions are almost always delayed prior to seizure onset and evolve into severe, persistent impairment. Thus, KCNB1 mutations are associated with diffuse brain dysfunction combining seizures, motor, and cognitive impairment.